Human Metapneumovirus in Children, Singapore - Liat Hui Loo (Emerging Infectious Diseases, 2007)
Four hundred specimens were collected from pediatric patients hospitalized in Singapore; 21 of these specimens tested positive for human metapneumovirus (HMPV), with the A2 genotype predominating. A 5% infection rate was estimated, suggesting that HMPV is a significant cause of morbidity among the pediatric population of Singapore.